The Sustainable Pig Nutrition by Partial Replacement of Soybean Meal with Copra Meal - D Amornlerdpison; L C Hsia; W Jantasin; C Thomtisang (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The sustainability of the pig industry can be improved through nutrition by increasing efficiency in an environmentally friendly environment. Alternative feed ingredients from agricultural waste or industrial by-products have attracted sustainable pig production systems. This study aimed to investigate the effects of sustainable pig nutrition by partially replacing soybean meal with copra meal. A total of 18 crossbred (L.Y.D.) growing female pigs were reared under three dietary treatments. Treatments were 1) corn-soybean meal diet (CON), 2) white copra meal, and 3) brown copra meal. The experimental results indicated no significant difference (P>0.05) in feed intake and weight gain for pigs fed the three experimental diets. However, pigs fed the white copra meal diet tended to have better feed intake than brown copra meal treatment. At week 2 of the experimental period, pigs fed copra meal diets had better feed efficiency than the CON diet (P<0.001). In conclusion, sustainable pig nutrition with copra meal may be used as an alternative for partial soybean meal in pig diets.